ECOLOGICAL AND ECONOMIC PROBLEMS OF AGRICULTURAL LAND IN THE REPUBLIC OF KALMYKIA - G. M. Borlikov; T. I. Bakinova; A. G. Zelensky (Юг России: экология, развитие)
Aim The aim is to analyze the ecological, economic and social issues of land use and to define organizational and economic measures to improve its effectiveness. Methods. We used scientific methods: comparison, generalization, analysis, synthesis, induction, deduction, system methods etc., as well as specific scientific methods: economic and mathematical, statistical, expert assessments, and others. On the basis of these methods we have carried out ecological and geographical, ecological and economic analysis in historical perspective, evaluating the degree of the influence of natural and anthropogenic factors on the degradation of agricultural land and efficiency of land use in general. Thus it revealed that the main problems of land-use issues in Kalmykia and possible ways to resolve the problem. Results. Regional studies of ecological and economic problems of land use, the study of the historical experience of grazing industry, the assessment of the current state of arid areas have allowed developing mechanisms for land management and environmental protection, preventing negative social and economic consequences. Conclusions. The present state of agricultural land in the Republic of Kalmykia has led to a significant change in the direction of deterioration of fragile arid ecosystems, which explains the decrease in the total ecological and socio-economic effects, manifested in the reduction of all benefits received by the population. Solving the problems identified above requires an effective economic mechanism of rational land use and environmental protection in the arid zone, which includes science-based land-use regulations, an effective system of land management, a set of measures to prevent further degradation of natural ecosystems.